The mediating effect of perceived behavioural control on the relationship between zakat law enforcement and intention to pay zakat - Adamu, Sani; Saad, Ram Al Jaffri (2015)
This paper aims to propose a conceptual framework for examining the influence of mediating effect of perceived behavioural control on the relationship between zakat law enforcement and intention to pay zakat among Muslim in State of Kano, Nigeria. An extensive literature review method was utilized to identify and analyse relevant literatures in order to propose the conceptual framework. This paper proposed framework to show those relationship. Theoretical and practical implications of the paper as well as suggestions for future research were also discussed.